Cultivating Compassion and Reducing Stress and Mental Ill-Health in Employees—A Randomized Controlled Study - Andersson, Christina; Mellner, Christin; Lilliengren, Peter; Einhorn, Stefan; Bergsten, Katja Lindert; Stenström, Emma; Osika, Walter (Frontiers in Psychology, 2022)
Stress and mental ill-health carry considerable costs for both individuals and organizations. Although interventions targeting compassion and self-compassion have been shown to reduce stress and benefit mental health, related research in organizational settings is limited. We investigated the effects of a 6-week psychological intervention utilizing compassion training on stress, mental health, and self-compassion. Forty-nine employees of two organizations were randomly assigned to either the intervention (n = 25) or a physical exercise control condition (n = 24). Multilevel growth models showed that stress (p = .04) and mental ill-health (p = .02) decreased over three months in both groups (pre-intervention to follow-up: Cohen’s d = –0.46 and d = 0.33, respectively), while self-compassion only increased in the intervention group (p = .03, between group d = .53). There were no significant effects on life satisfaction in any of the groups (p > .53). The findings show promising results regarding the ability of compassion training within organizations to decrease stress and mental ill-health and increase self-compassion.